2015
DOI: 10.1371/journal.pone.0116747
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Dose of Doxorubicin Is Required to Alter the Gene Expression Profiles in MCF-7 Cells Acquiring Multidrug Resistance

Abstract: Cellular mechanisms of multidrug resistance (MDR) are related to ABC transporters, apoptosis, antioxidation, drug metabolism, DNA repair and cell proliferation. It remains unclear whether the process of resistance development is programmable. We aimed to study gene expression profiling circumstances in MCF-7 during MDR development. Eleven MCF-7 sublines with incremental doxorubicin resistance were established as a valued tool to study resistance progression. MDR marker P-gp was overexpressed only in cells term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 51 publications
4
56
0
3
Order By: Relevance
“…The phosphoinositide 3-kinase/serine-threonine kinase (PI3K/Akt) signaling pathway is a well-known fundamental intracellular signaling transduction pathway involved in multiple biological processes both in normal and cancer cells, including gene transcription and translation, cell growth, proliferation and survival, cell metabolism, cell cycle progression, apoptosis and autophagy (8)(9)(10). Besides, there is an increasing amount of preclinical data supporting that the PI3K/Akt signaling pathway is also involved in the drug resistance of different types of human malignant cells, including CML (2,4,5,(12)(13)(14)(15). A previous study demonstrated that the resistant CML cell line K562/ADM presented higher PI3K/ Akt activity than the sensitive one and was in accordance with the MDR phenotype (2).…”
Section: Introductionmentioning
confidence: 99%
“…The phosphoinositide 3-kinase/serine-threonine kinase (PI3K/Akt) signaling pathway is a well-known fundamental intracellular signaling transduction pathway involved in multiple biological processes both in normal and cancer cells, including gene transcription and translation, cell growth, proliferation and survival, cell metabolism, cell cycle progression, apoptosis and autophagy (8)(9)(10). Besides, there is an increasing amount of preclinical data supporting that the PI3K/Akt signaling pathway is also involved in the drug resistance of different types of human malignant cells, including CML (2,4,5,(12)(13)(14)(15). A previous study demonstrated that the resistant CML cell line K562/ADM presented higher PI3K/ Akt activity than the sensitive one and was in accordance with the MDR phenotype (2).…”
Section: Introductionmentioning
confidence: 99%
“…MCF-7 cells were less sensitive to the NP treatment. Studies have already demonstrated the induction of resistance in MCF-7 cells (Tsou et al 2015). This feature in these cells can be related to data from the viability assay, which demonstrated a milder action on cytotoxicity over time.…”
Section: Discussionmentioning
confidence: 58%
“…Table S3 Changes in cellular morphology served as an endpoint for generation of resistant cell lines, as well as a reason for focusing on EMTrelated features. 52,53 Using the drug to which cells are sensitive (eg, the cisplatin on A2780 or doxorubicin on A280Cis) the CSC, MDR, and EMT-related genes are upregulated. Both drug-resistant cell lines exhibited the downregulation of CDH1 and upregulation of EMT transcription regulators SNAI1, SNAI2, and ZEB1 at mRNA level.…”
Section: Alterations In the Macrophage Expression Profile In Responmentioning
confidence: 99%
“…Cytostatic drugs were shown to induce the stem cell markers in ovarian cancer cells in the short term, 50,51 as well as selectively enrich for CSCs under continuous drug treatment. 52,53 Using the drug to which cells are sensitive (eg, the cisplatin on A2780 or doxorubicin on A280Cis) the CSC, MDR, and EMT-related genes are upregulated. Therefore, even a single dose of the drug may cause a significant change toward activating EMT, CSC, MDR profile, as previously reported.…”
Section: Mechanisms Of Drug Cross-resistance In A2780-derived Cell Linesmentioning
confidence: 99%